2017
DOI: 10.1159/000477479
|View full text |Cite|
|
Sign up to set email alerts
|

MALAT1 Modulates TGF-β1-Induced Endothelial-to-Mesenchymal Transition through Downregulation of miR-145

Abstract: Background/Aims: Endothelial-to-mesenchymal transition (EndMT) plays significant roles under various pathological conditions including cardiovascular diseases, fibrosis, and cancer. EndMT of endothelial progenitor cells (EPCs) contributes to neointimal hyperplasia following cell therapy Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA (lncRNA) that promotes metastasis and cancer. MicroRNA-145 (miR-145) is a tumor suppressor that has been reported to inhibit SMAD3-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 67 publications
4
81
0
Order By: Relevance
“…EndMT can be induced by multiple factors via several interactive signaling pathways. The key factor in EndMT is the TGF-β super family that plays an indispensable role [14, 41]. This study demonstrated that H 2 O 2 -mediated oxidative stress induced EndMT in HAECs as indicated by the marked increases in the expression of mesenchymal cell marker genes and concordant decreases in endothelial cell marker genes, and these EndMT-related changes were abolished by LIPUS, indicating the anti-EndMT property of this ultrasound treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…EndMT can be induced by multiple factors via several interactive signaling pathways. The key factor in EndMT is the TGF-β super family that plays an indispensable role [14, 41]. This study demonstrated that H 2 O 2 -mediated oxidative stress induced EndMT in HAECs as indicated by the marked increases in the expression of mesenchymal cell marker genes and concordant decreases in endothelial cell marker genes, and these EndMT-related changes were abolished by LIPUS, indicating the anti-EndMT property of this ultrasound treatment.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, accumulation of reactive oxygen species (ROS) can directly damage endothelial cells and indirectly modulate endothelial cell function via altering expression and function of the related genes [13]. EndMT is a cellular process where endothelial cells undergo significant morphological changes with loss of their endothelial characteristics and gain of mesenchymal properties that ultimately leads to transformation into stromal fibroblasts [14]. …”
Section: Introductionmentioning
confidence: 99%
“…One previous study [31] also reported that the TGFβ1-smad signaling pathway is an important up-stream mechanism of EMT. Meanwhile, the TGFβ1-smad is positively correlated with the IL-33 expression.…”
Section: Discussionmentioning
confidence: 86%
“…However, a recent study showed that TGF-β mediated EMT in retinal pigment epithelium through complex interplay between Smad pathway, Akt, p38MAPK, ERK1/2 pathways and Jagged/Notch pathway [26]. In addition, miR-145 was recently reported to modulate TGF-β1/Smad3 signaling to regulate endothelial-to-mesenchymal transition [27]. Further studies are necessary to investigate the crosstalk of Smad pathway with other pathways in mediating EMT of alveolar epithelial cells exposed to ER stress.…”
Section: Discussionmentioning
confidence: 99%